2022
DOI: 10.1017/s0022215122000469
|View full text |Cite
|
Sign up to set email alerts
|

Lateral cystic neck masses in adults: a ten-year series and comparative analysis of diagnostic modalities

Abstract: Background In adults, the solitary lateral cystic neck mass remains a diagnostic challenge with little solid material to target for cytology and few clues on imaging modalities to suggest underlying malignancy. Method This study was a retrospective review of patients presenting with a lateral cystic neck mass to a tertiary academic head and neck centre over a 10-year period. Results A total of 25 of 157 cystic lesions were subsequently malignant on paraffin section hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated an elevated risk of malignancy in patients of male gender and advancing age. 8,[18][19][20][21][22][23][24][25] Until now, however, to the authors' knowledge, there has not been a multivariate tool to calculate a tailored risk for an individual patient presenting to a clinician using only their demographic data, as well as their initial ultrasound scan and FNAC results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated an elevated risk of malignancy in patients of male gender and advancing age. 8,[18][19][20][21][22][23][24][25] Until now, however, to the authors' knowledge, there has not been a multivariate tool to calculate a tailored risk for an individual patient presenting to a clinician using only their demographic data, as well as their initial ultrasound scan and FNAC results.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is no consensus on the optimal steps with regard to imaging patients with lateral cervical cystic masses and an indolent primary site, a recent study by Jones et al found that the addition of cross-sectional imaging via craniofacial MRI increased sensitivity from 25.00 per cent (ultrasound scanning and FNAC alone) to 40.75 per cent, increased the positive likelihood ratio from 3.22 to 3.49, reduced the negative likelihood ratio from 0.81 to 0.67 and did not significantly affect the accuracy (80.49 per cent, 95 per cent CI = 73.59-86.25). 24 With its growing availability, MRI use in the diagnostic pathway for SCC with an unknown primary tumour has significantly increased over time, 27 and indeed has recently been demonstrated to be of particular use in the detection of small oropharyngeal tumours with p16 positive nodal disease, 28 which represent a large proportion of this cohort. This, coupled with the lack of exposure to ionising radiation, makes craniofacial MRI a pertinent choice of next investigation in low-risk patients (5-15 per cent) before proceeding to cyst excision (with or without rigid endoscopic assessment of the upper aerodigestive tract).…”
Section: Development Of Risk-stratified Treatment Pathwaysmentioning
confidence: 99%
“…[4][5][6][7] Solitary cystic neck metastasis (SCNMets) is a well-recognized clinical entity observed in various head and neck cancers; however, in approximately 85% of cases, the primary tumor originates from the epithelium within Waldeyer's ring. 8,9 According to research conducted by Huang et al, 10 it was found that nodal metastasis from HPV+ and HPV− oropharyngeal SCC had a cystic appearance in 39.4% and 18.5% of cases, respectively. Two main pathogenic mechanisms in the substrate of SCNMets have been identified so far: true cystic changes originating from malignant cells or transformed keratinocytes, which have intrinsic properties for cyst formation (type 1) and pseudocystic transformation resulting from the spontaneous degradation of keratin and cellular debris within carcinomatous lymph node deposits or the blockage of lymphatic fluid flow passing through a metastatic (type 2) node.…”
mentioning
confidence: 99%
“…Solitary cystic neck metastasis (SCNMets) is a well-recognized clinical entity observed in various head and neck cancers; however, in approximately 85% of cases, the primary tumor originates from the epithelium within Waldeyer’s ring 8,9 . According to research conducted by Huang et al, 10 it was found that nodal metastasis from HPV+ and HPV− oropharyngeal SCC had a cystic appearance in 39.4% and 18.5% of cases, respectively.…”
mentioning
confidence: 99%
“…6,7 The Journal 'paper of the month' for March 2023 is a large study of lateral neck masses from Liverpool (UK), which includes 157 cases over 10 years in a large tertiary head and neck centre. 8 Twenty-five of these cases turned out to be malignant on histology (23 squamous carcinoma and 2 differentiated thyroid cancer). The ipsilateral tonsil was the commonest site of an occult primary tumour in patients with neck metastasis.…”
mentioning
confidence: 99%